2018
DOI: 10.1111/jne.12568
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for effective structure‐based neuromodulatory effects of new analogues of neurosteroid allopregnanolone

Abstract: The neurosteroid allopregnanolone (AP) modulates neuroendocrine/neurobiological processes, including hypothalamic-pituitary-adrenocortical activities, pain, anxiety, neurogenesis and neuroprotection. These observations raised the hope of developing AP-based therapies against neuroendocrine and/or neurodegenerative disorders. However, the pleiotropic actions of AP, particularly its cell-proliferation-promoting effects, hamper the development of selective/targeted therapies. For example, although AP-induced neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Moreover, the action of APα has been shown to activate GABAAR-driven VGLCC and subsequent increases of intracellular Ca 2+ concentration (Keller et al, 2004;Wang et al, , 2010Wang and Brinton, 2008;Jagasia et al, 2009;Chen S. et al, 2011;Frye et al, 2014), which was in accordance with our current study. In addition, we also cannot rule out the possibility that APα interacts with the pregnane-X-receptor or membrane progesterone G-protein coupled receptor to regulate its neuroprotective process (Charalampopoulos et al, 2008;Mendell et al, 2018;Taleb et al, 2018). Mendell et al (2018) also suggested a model for neurosteroid actions included both GABAAR-dependent and GABAAR-independent mechanisms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the action of APα has been shown to activate GABAAR-driven VGLCC and subsequent increases of intracellular Ca 2+ concentration (Keller et al, 2004;Wang et al, , 2010Wang and Brinton, 2008;Jagasia et al, 2009;Chen S. et al, 2011;Frye et al, 2014), which was in accordance with our current study. In addition, we also cannot rule out the possibility that APα interacts with the pregnane-X-receptor or membrane progesterone G-protein coupled receptor to regulate its neuroprotective process (Charalampopoulos et al, 2008;Mendell et al, 2018;Taleb et al, 2018). Mendell et al (2018) also suggested a model for neurosteroid actions included both GABAAR-dependent and GABAAR-independent mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, all reagents, materials, and chemicals were analytical grade and highest purity, including human neuroblastoma SH-SY5Y cell lines (SCSP-5014, Chinese Academy of Sciences, China); Dulbecco's modified Eagle's medium (DMEM, 11965092), Neurobasal (21103049), B27 (17504044), fetal bovine serum (FBS), glutamax (35050061), trypsin-EDTA (25300062) and sodium pyruvate (11360070; Gibco Invitrogen, MA, USA); APα (3653) and Bic (485494; Tocris, USA); Nifedipine (ab120135, Abcam, Burlingame, CA, USA); RA (R2500) and 6-OHDA (H4381; Sigma-Aldrich, St. Louis, MI, USA); penicillin and streptomycin (Solarbio, Beijing, China); bovine serum albumin (BSA) and BrdU (Bio-Sharp, China); DMSO (ST038), EGTA (ST068), phenylmethanesulfonyl fluoride (PMSF, ST506), TritonX-100, cytosolic and nuclear extraction kit (P0028; Beyotime, China). The concentration of key chemicals was chosen according to the relevant references (Liu et al, 2002;Miloso et al, 2004;Wang et al, , 2010Gilany et al, 2008;Wang and Brinton, 2008;Fernandes et al, 2017;Xie et al, 2017;Taleb et al, 2018). All experiments should comply with the standard biosecurity and safety procedures from the ethical committee of Wenzhou Medical University according to the National Institute of Health Guide for Care and Use of Laboratory Animals (NIH Publications No.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Neurosteroid ALLO has been reported to induce the proliferation of different cell types [ 37 , 38 ]. This parameter is important in the context of autoimmune diseases, where an uncontrolled proliferation of immune cells could exacerbate the inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Steroid hormones are known to modulate cell proliferation. ALLO has also been reported to increase the proliferation of different cell types, such as postnatal hippocampal cells [ 37 ], SH-SY5Y cells [ 38 ], or Schwann cells [ 80 ]. Neither the microglial BV-2 nor the oligodendroglial 158N cell line used in this study showed a modified proliferation after the administration of ALLO in the range of 10 nM to 10 µM ( Figure 3 C,D or Figure 6 C).…”
Section: Discussionmentioning
confidence: 99%
“…The last paper in this section is an experimental study describing the properties of BR297 (a new analogue of allopregnanolone) that appears to be a potent neuroprotective compound devoid of cell‐proliferative activity. These results open promising perspectives for the development of neurosteroid‐based selective and effective strategies against neuroendocrine and/or neurodegenerative disorders …”
mentioning
confidence: 98%